Penggunaan Bikatein Dalam Ransum terhadap Bobot Hidup, Persentase Bobot Karkas, Hati Dan Ginjal Ayam Broiler - Retnani, Yuli; Nurlaila, Nurlaila; Suryahadi, Suryahadi (Fakultas Peternakan Universitas Jambi, 2009)
The provision of cheap food and good quality needs to be done because the cost of food is the biggest cost is about 60-70% of the total production costs. Cassava Bikatein is rich in proteins obtained from cassava fermented with Aspergillus niger. Bikatein expected to be one feed protein sources. The purpose ofthis study was learn about the use of bikatein on percentage body weight, carcass, liver and kidney of broiler chicken. This research used 200 DOC shaver starbro strain unsexed. Design used in the experiment was Completely Randomized Design (RAL) with four treatments and five replications. Eachevery replicated use ten-broiler chicken. The treatments was different of addition bikatein in the broiler chicken are 0 (R0), 5 (R1), 10 (R2) and 15% (R3). The variable that observed was percentage body weight, carcass, liver and kidney of broiler chicken. The result showed that using bikatein 15% in ration were not significant on percentage body weight, liver and kidney. The using bikatein 10 and 15 % influence on percentage carcass. The conclusion was the treatment can to used in ration without endanger health broiler chicken as 5%.